Medial amygdala ERα expression influences monogamous behaviour of male prairie voles in the field. Issue 1956 (11th August 2021) - Lambert, Connor T.; Lichter, James B.; Perry, Adam N.; Castillo, Samuel A.; Keane, Brian; Cushing, Bruce S.; Solomon, Nancy G.
Abstract : Formation of long-term pair-bonds is a complex process, involving multiple neural circuits and is context- and experience-dependent. While laboratory studies using prairie voles have identified the involvement of several neural mechanisms, efforts to translate these findings into predictable field outcomes have been inconsistent at best. Here we test the hypothesis that inhibition of oestrogen receptor alpha (ERα) in the medial amygdala of male prairie voles would significantly increase the expression of social monogamy in the field. Prairie vole populations of equal sex ratio were established in outdoor enclosures with males bred for high levels of ERα expression and low levels of prosocial behaviour associated with social monogamy. Medial amygdala ERα expression was knocked down in half the males per population. Knockdown males displayed a greater degree of social monogamy in five of the eight behavioural indices assessed. This study demonstrates the robust nature of ERα in playing a critical role in the expression of male social monogamy in a field setting.